Sistem Pemberhentian (Impeachment) Kepala Daerah Di Era Demokrasi Langsung (Sebuah Kajian Teoritik-Ketatanegaraan) - aziz hakim (Jurnal Hukum IUS QUIA IUSTUM, 2006)
The Impeachment System implemented in Law No. 32 cm the Year 2004 still uses representative mechanism with centralistic nature. The systemis controvercial with direct democratic values. However, referendum can be used as an ideallegal mechanism imposed on the head of region impeachment.